Gonadal dysgenesis and hermaphroditism - Hoffenberg, Raymond (Department of Medicine, 2020)
This thesis has developed from a study of a series of patients with a gonadal dysgenesis. Shortly after the inception of the study, Pelani and his co-workers (1954) published a report on the nuclear chromatin pattern in three cases of the syndrome. Their findings provided one of the most illuminating contributions made in the field of endocrinology and have stimulated a new approach to the problem of semal differentiation.